Avaliação físico-química, planctônica e microbiológica do Rio Uruguai médio, região de Uruguaiana, RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The Uruguay River is one of the main rivers of Rio Grande do Sul, having a length of 1770 kilometers and an altitude of 400 meters in the border of the states of Santa Catarina and Rio Grande do Sul. The city of Uruguaiana is the main city of Rio Grande do Sul that is bathed by its waters and the population of Uruguaiana and region, which uses the waters of the river for different purposes, ranging from recreation to direct use of untreated water. Thus, this study aimed to evaluate the water quality based on the physical and chemical, planktonic and microbiological parameters of the river. The present work was conducted in the Nucleus of Ichthyological, Limnological and Aquaculture Research of the Uruguay River Basin (NUPILABRU), together with the Food Microbiology laboratory of the Federal University of Pampa - Campus Uruguaiana, from September to November 2016, totaling a period Three months. Three points were collected near the Uruguay River International Bridge, where some parameters, such as ammonia, nitrite, alkalinity, hardness, air and water temperature and transparency were analyzed at the site of collection, and other parameters, including oxygen dissolved, pH, electrical conductivity and turbidity, in addition to the quantification of the planktonic community, were analyzed in the NUPILABRU laboratory of the Federal University of Pampa - Campus Uruguaiana. At the same university, in the laboratory of Microbiology of the Food, the microbiological parameters of the samples were evaluated for the indices of fecal coliforms and total coliforms by the multiple tube method. All the results obtained were compared to water quality standards in Resolution No. 20 of the National Environmental Council of 1986. Among the physical-chemical results, it was observed that only the parameter of ammonia and turbidity were above the values recommended by the resolution. Among the planktonic results we observed the presence of (micro) organisms sensitive to water quality. Regarding the microbiological results, it was observed that the total coliform and coliform indices vary throughout the collections, but considering the water quality evaluation criteria by the resolution, when analyzing 80% of the samples, it can be Classified as Class II water, and satisfactory for bathability. Our work constitutes an important source of knowledge about the water quality of the river for the population of Uruguaiana and region and the data generated are upward from the perspective that can be used in future analyzes, to compare the studied patterns and improvement of the Sanitary conditions of the municipality.
Physical-chemical, plancontal and microbiological evaluation of the Uruguay medium river, Uruguaiana region, RS
Keywords: Aquaculture; Microbiology; Plankton; Uruguay river; Pampa Brazilian; CNPQ::CIENCIAS AGRARIAS; Aquicultura; Microbiologia; Plâncton; Rio Uruguai; Pampa brasileiro